Pengaruh Pengetahuan Akuntansi Dan Kinerja Karyawan Terhadap Kualitas Laporan Keuangan - Ajeng Wijayanti; Susi Ariyani (Owner : Riset dan Jurnal Akuntansi, 2022)
This study aims to analyze the effect of accounting knowledge and employee performance on the quality of financial reports moderated by the use of Accounting Information Systems in service companies in the Greater Jakarta area. The population of this research is employees who work in companies in the service sector in the Greater Jakarta area. The research sample consisted of 153 respondents. The data used in the form of primary data, namely by distributing online questionnaires to employees who work in service companies in the Jabodetabek area. The data collection technique used in this research is probability sampling. The statistical method uses Multiple Linear Regression Analysis, with statistical test hypothesis testing. Using SPSS and Smart PLS programs. This study applies a Likert scale with a 5 point scale to measure research variables. The results showed that accounting knowledge, employee performance and accounting information systems had a significant effect on the quality of financial reports, AIS Moderation on the effect of Accounting Knowledge on the quality of financial statements produced no significant effect, and AIS Moderation on Employee Performance on the quality of financial statements does not have a significant effect. The implication of this research is that companies can use this research in order to maintain and improve the quality of financial reports that are good and according to standards for the benefit of management and stakeholders in making future decisions by increasing knowledge and performance of their employees.